ANALISIS RESEPSI PADA CHANNEL YOUTUBE GAMING “ KIMI HIME” - Setyo Eka Rofi; Wiwid Noor Rakhmad (Interaksi Online, 2020)
Appearance in a video is watched by being seen or polite society and it is to be done by a youtuber in indonesia. Kimberly Khoe or often invoked in social networking youtube kimi hime where every his always using open and indicating one part his body which can help draw attention to most of man still have popularity high for a player gim on youtube, although appear news and a petition and showing gave internet users in Indonesia. Research perception to know the audience to channel video on youtube Kimi Hime. Theory used for this study is a theory reception analysis Stuart Hall. Type research qualitative study used is the type 5 people from one subject men and women having intensity often also accessed the interaction youtube video providers, or seen channel game on youtube was 20 and 25 years with age has included adult and not youth. Then analysis data was undertaken to find preferred reading. Based on the research and analysis undertaken, so the audience Kimi Hime to video that is on youtube are mostly respondents position himself as oppositional-reading, because vulgar an impressed in her appearance. Limitations in this study is the theory used in this research only one that is the reception analysis theory Stuart Hall. For the next research, required to be added other theory as a supporter of reception analysis theory Stuart Hall.